Promoting Collaborations Between Radiologists and Medical Physics: Bridging Expertise for Enhanced Patient Care - Rakan Mohmmed Hassan Almusawi, Afrah Sagheer Mobarak ALtofiq, Shaykhah Hanash Al Jawtar, Nada Hassan Nasser Al Mustaneer; Hussain Omar Alnaeli, Dahma Najeeb Saeed Alyami, Bashayr Dimshaq Edah Alyami, Aishah Hassan Assiri (Journal of International Crisis and Risk Communication Research, 2024)
Collaboration between radiologists and medical physicists plays a pivotal role in enhancing the accuracy of medical imaging and improving patient safety. This review explores the importance of the dynamic partnership between radiologists and medical physicists, emphasizing their complementary roles in improving healthcare outcomes. Radiologists oversee clinical interpretations, while medical physicists focus on ensuring imaging quality, safety, and compliance with regulatory standards. Key areas of synergy include image quality improvement, dose management, technology integration, and patient education. Future trends highlight the integration of artificial intelligence, multimodality imaging, and advanced data analytics, reinforcing the need for a multidisciplinary approach. Collaboration between radiologists and medical physicists enhances the ability of healthcare systems to achieve innovative, effective, and patient-centered imaging practices.